MEMORY OF THE SOVIET PERIOD IN MOLDOVA: INFLUENCE OF SOCIAL TRAUMA AND CONTEMPORARY POLITICS - Anna Vichkitova (Economy and Sociology)
This study explores the memory of the Soviet period in Moldova, focusing on how social trauma and contemporary politics influence perceptions of the past. Utilizing oral history methods, over 60 interviews were conducted in Moldova during the latter half of 2023, encompassing a diverse range of respondents aged from their 20s to 90s. The research spans various regions including northern Moldova, Chisinau, Gagauzia, and Transnistria. The findings reveal that memories of the Soviet era are often characterized by nostalgia, shaped significantly by the abrupt collapse of the USSR and the subsequent social and economic turmoil. This nostalgia is interpreted through the lens of cultural trauma theory, as proposed by Jeffrey Alexander and Piotr Sztompka, highlighting the profound societal changes that followed the Soviet disintegration. The study shows that the rhetoric of the USSR, playing a significant role in Moldovan politics and being instrumentalized by both proponents and opponents of Eurointegration, also greatly influences the image of the Soviet era among the Moldovan population. The ongoing economic and social crises, coupled with recent geopolitical tensions, have further intensified the nostalgic sentiments towards the Soviet era. In conclusion, the enduring social trauma and the continuous political invocation of Soviet rhetoric have a profound impact on the collective memory of the USSR in Moldova.